The Consequences of Academic Match between Students and Colleges - Eleanor Wiske Dillon; Jeffrey Andrew Smith (Center for Economic Studies and ifo Institute (CESifo), 2017)
We consider the effects of student ability, college quality, and the interaction between the two on academic outcomes and future earnings using data on two cohorts of college enrollees drawn from the NLSY-79 and the NLSY-97. We find that student sorting has increased modestly between cohorts, and that student ability and college quality strongly improve degree completion and earnings. These patterns imply that, on average, students benefit from “overmatch” of the sort generated by affirmative action in admissions. We find little evidence of match effects on degree completion at eight years or on STEM degree completion, but suggestive evidence of some complementarity between student ability and college quality in degree completion at four years and long-term earnings. Such complementarity implies a tradeoff between equity and efficiency for policies that move lower ability students to higher quality colleges.
Keywords: J31; I24; 330; college mismatch; college quality